2010
DOI: 10.1007/s10641-010-9751-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of developmental temperature on swimming performance of zebrafish (Danio rerio) juveniles

Abstract: It is widely known that water temperature affects the swimming capacity of fish. But the effect of the rearing temperature on the swimming ability of the fish at later stages, has not had similar attention. In this study, four populations of zebrafish, were reared in different water temperatures (22, 25, 28 and 31°C) and after being acclimatized in a common temperature (26.5°C) for over a month, they were subjected to swimming trials in order to evaluate the maximum relative critical velocity (RU crit ) in eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 66 publications
3
34
0
2
Order By: Relevance
“…Because fish were of similar body length and mass (Table S3), there was most likely a change in body shape. However, the magnitude of this change differed between T E groups, in accordance with previous observations that T E affects body shape (20). The different responses to cold were reflected by significant T A × T E interactions for total muscle area and the total transverse area of fast fibers (P = 0.006 and P = 0.040) and by the cold-induced increases in total muscle, slow fiber, and fast fiber transverse areas in only the 22°C and 32°C T E groups.…”
Section: Embryonic Temperature Affects Thermal Acclimation Of Musclesupporting
confidence: 91%
“…Because fish were of similar body length and mass (Table S3), there was most likely a change in body shape. However, the magnitude of this change differed between T E groups, in accordance with previous observations that T E affects body shape (20). The different responses to cold were reflected by significant T A × T E interactions for total muscle area and the total transverse area of fast fibers (P = 0.006 and P = 0.040) and by the cold-induced increases in total muscle, slow fiber, and fast fiber transverse areas in only the 22°C and 32°C T E groups.…”
Section: Embryonic Temperature Affects Thermal Acclimation Of Musclesupporting
confidence: 91%
“…In spite of its popularity as a research tool, only recently did some integrated studies about its biological and ecological characteristics emerge (Engeszer et al 2007;Spence et al 2008) which however do not complete the puzzle of knowledge regarding its early life conditions and especially the environmental temperature. Although the temperature of the species' habitat seems to be established at the range from 6°C in the winter up to 38°C in the summer (Spence et al 2008) there are still some contradictions concerning the temperature range in which reproduction and early development take place (Sfakianakis et al 2011). Our personal observations throughout many rearing trials showed that the rearing temperatures of 22°C and 31°C are the lower and upper limit values respectively for successful rearing in the laboratory.…”
Section: Introductionmentioning
confidence: 71%
“…These findings are in juxtaposition to previous findings on the effects of developmental temperature on aerobic performance in zebrafish. Sfakianakis et al () found that zebrafish reared at four different temperatures (22°C, 25°C, 28°C, and 31°C) had differential sustained aerobic swim performance when acclimated to one common median temperature (26°C). Individuals reared at 22°C had lower average relative critical swim speeds ( RU crit ) than those reared at the three higher temperatures, although the only significant difference seen was at 31°C (Sfakianakis et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Sfakianakis et al () found that zebrafish reared at four different temperatures (22°C, 25°C, 28°C, and 31°C) had differential sustained aerobic swim performance when acclimated to one common median temperature (26°C). Individuals reared at 22°C had lower average relative critical swim speeds ( RU crit ) than those reared at the three higher temperatures, although the only significant difference seen was at 31°C (Sfakianakis et al, ). Our finding that within a similar temperature range burst swim performance is unaffected suggests a differential effect of developmental temperature on aerobic and anaerobic performance.…”
Section: Discussionmentioning
confidence: 99%